Exploration of molecular interaction in binary liquid mixtures of dipropylene glycol dimethyl ether with methyl acetoacetate and ethyl acetoacetate at different temperatures using physicochemical approach. (October 2020) - Kumar, Harsh; Akanksha,
Highlights: New density and speed of sound data for DPGDME + alkyl acetoacetate binary liquid mixtures. Negative deviations in excess molar volumes suggest packing of structure. Negative excess isentropic compressibilities predicts strong interactions. Excess thermal expansion coefficient also suggest strong interaction between unlike species. Shift in the wavenumber of stretching bands in binary mixtures. Abstract: Density ρ, and speed of sound u, measurements have been carried out for the binary mixtures of dipropylene glycol dimethyl ether with methyl acetoacetate and ethyl acetoacetate at intervals 5 K, from temperatures T = (288.15 to 308.15) K and experimental pressure of p  = 0.1 MPa. The entire ranges of composition have been measured using Anton-Paar DSA 5000 M densimeter i.e. density and speed of sound analyzer. Using experimental density data the excess molar volume, V m E has been determined. Isentropic compressibility along with excess molar compressibility have been determined from the experimental speed of sound. Deviations in intermolecular free length and deviations in acoustic impedance along thermal expansion coefficient have also been calculated. The variation of these parameters with composition and temperature have discussed in terms of molecular interaction in these mixtures. FT-IR studies of these mixtures have been also reported and obtained results have been used to analyze the mixing behaviour of the components.